PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP PEMAHAMAN KONSEP IPA KELAS V SEKOLAH DASAR - Kristiani, Imelda; Rosnita, Rosnita; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThis research aimed to determine how far the influence of the use of problem based learning model on comprehending the Natural Science concept at fifth grade students. The method of this reserch was an experimental research. Nonequivalent Control Group was used on this research. Sample of this research were 76 students, consisted of 35 male students and 32 female students. Measurement technique was used in collecting the data. The tool of data collecting was in a written test form which consists of 40 questions. The data were colledted by calculating the average of the pretest and posttest result. Based on the result calculation, it was found out that the average score of the control class wasÂ  61.4 and the average score of experimental class was 68.46 which hypothesis test using showed the t-test was 3.80 and t-table (Î± = 5%) was 1.67, it meant that tÂ_test (3.80) > t_table (1.67). It indicated that the altirnative hypothesis (Ha) was accepted which showed the Effect Size (ES) of the treatment was 0.6. It was categorized as medium. The result finding showed the use of problem based- learning model gave moderate effect on comprehending the natural science concept at fifth grade students of Sekolah Dasar Negeri 16 Pontianak Selatan.Keywords: Influence, Problem Based Learning Model, Science Conceft